Chemopreventive Role of Apigenin against the Synergistic Carcinogenesis of Human Papillomavirus and 4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone - Fangzheng Yin (Biomedicines, 2020)
Tobacco smoke and human papillomavirus (HPV) are both crucial causes of cancer, and their cooperative carcinogenesis has drawn more attention in recent years. Apigenin (AP), a typical flavonoid abundantly found in flowers of plants, vegetables, and fruits, has been demonstrated to exert an anti-carcinogenic effect on various types of cancer. In this study, we investigated the capability of AP against malignant transformation and DNA damage of immortalized human esophageal epithelial (SHEE) cells induced by the synergism of HPV18 and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK). The results indicated that the enhancement of migration, invasion, and proliferation ability of SHEE cells induced by HPV and NNK could be effectively inhibited by AP. Moreover, the levels of pyridyloxybutylated (POB)-DNA adducts induced by NNK via P450-catalyzed metabolic activation could also be significantly suppressed by AP. Further analyses on the molecular mechanism revealed that AP inhibited the synergistic carcinogenesis of NNK and HPV on SHEE cells by reducing the expression of mutp53, CDK4, Cyclin D1, and p-Rb (Ser 780), increasing caspase-3 activity, thereby arresting the cell cycle at G1 phase and promoting apoptosis of SHEE cells. We hypothesize that the decrease in NNK-induced POB-DNA adduct levels is related to the deactivation of P450 by AP, which needs to be confirmed in future studies. This study highlights that AP may be employed as a promising chemopreventive agent against cancers in smokers with an HPV infection.